Drone challenge: A platform for promoting programming and robotics skills in K-12 education. (4th January 2019) - Bermúdez, Aurelio; Casado, Rafael; Fernández, Guillermo; Guijarro, María; Olivas, Pablo
The development of skills related to computer programming and robotics and the introduction of computational thinking principles in high schools are worldwide trends today. An effective way of initiating young students in this world consists in proposing them stimulating challenges. This work presents a robotic platform that has been successfully used to develop a competition (called Drone Challenge ) in which students had to program the navigation system for a simulated unmanned aerial vehicle (or drone). Both the competition and the supporting platform are described in detail. In particular, the article provides a deep technical description of the main components of the platform, namely the drone simulator and the navigation development framework. The results of the survey conducted after the challenge point to the suitability of the working platform deployed.